2021
DOI: 10.3390/antiox11010094
|View full text |Cite
|
Sign up to set email alerts
|

Genoprotective Effect of Some Flavonoids against Genotoxic Damage Induced by X-rays In Vivo: Relationship between Structure and Activity

Abstract: Flavonoids constitute a group of polyphenolic compounds characterized by a common gamma-benzo- pyrone structure considered in numerous biological systems to possess antioxidant capacity. Among the different applications of flavonoids, its genoprotective capacity against damage induced by ionizing radiation stands out, which has been related to antioxidant activity and its chemical structure. In this study, we determined the frequency of appearance of micronucleus in vivo by means of the micronucleus assay. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…Thereby, differences in ROS scavenging potential can be attributed to the different functional groups attached to the main nucleus [ 100 ]. Intercalation in DNA double helices induces stabilization and condensation of DNA structures making them less susceptible to free radicals’ attack [ 100 ], reducing genotoxic damage induced by IR [ 101 ]. Xanthine oxidase and lipoxygenase are inhibited by many polyphenols, thus reducing the generation of free radicals.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Thereby, differences in ROS scavenging potential can be attributed to the different functional groups attached to the main nucleus [ 100 ]. Intercalation in DNA double helices induces stabilization and condensation of DNA structures making them less susceptible to free radicals’ attack [ 100 ], reducing genotoxic damage induced by IR [ 101 ]. Xanthine oxidase and lipoxygenase are inhibited by many polyphenols, thus reducing the generation of free radicals.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…We used these three different cytogenetic assays in a complementary way to confirm the genotoxic capacity of X-rays by determining the frequency of appearance of MN in irradiated human lymphocytes and in animals exposed to ionizing radiation. On the other hand, a reduction of this MN frequency confirms the protective capacity (antigenotoxic effect) of CA against damage induced by ionizing radiation [38][39][40][41]. In addition, it was possible to determine the in vivo and in vitro genotoxic effects of irradiated serum from recipient animals and irradiated medium obtained from irradiated cultures cells, respectively, in order to characterize the RIBE [32].…”
Section: Discussionmentioning
confidence: 81%
“…Our data showing an OLC-mediated reduction in radiation-induced genotoxicity, expressed in the form of MN scored in normal BN cells ( Figure 6 ), are in keeping with similar findings that have been scantly reported over a long time on the radioprotection afforded by polyphenols to irradiated cellular DNA using the same endpoint. Thus, while, almost twenty years ago, Greenrod and Fenech [ 70 ] had assessed the impact of several wine-derived polyphenols on human lymphocytes irradiated in vitro by the CBMN assay reporting an anti-genotoxic action, Alcaraz et al [ 71 ] very recently reported on the radioprotective effect by flavonoids in mice whole-body irradiated with 0.5 Gy of γ-radiation assessed by MN formation in polychromatic erythrocytes. More specifically, another recent work by Amani et al [ 72 ] found that 100 mM of oleuropein afforded protection from apoptosis, clastogenicity, and genotoxicity, with the latter measured by MN occurrence, in human cultured lymphocytes exposed to a single dose of 2 Gy of γ-rays.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation would add to such a higher “background” oxidative stress in cancer cells. As suggested by Alcaraz et al [ 71 ], under certain conditions depending, among other factors, on the number and positions of hydroxyl groups, polyphenolic compounds through the chelation of chromosome-associated metal ion Cu 2+ can switch from an anti-oxidant to a pro-oxidant activity, a mechanism already postulated to explain flavonoid-mediated DNA damage [ 77 ]. Thus, it is possible that, in normal cells, the additional level of ROS produced by radiation can be dealt with effectively by the anti-oxidant scavenging ability of the oleuropein-rich OLC at the concentration used in this study, whereas the peculiar redox status of cancer cells combined with the mentioned properties of oleuropein and the additional radiation-induced ROS could reverse the same amount of OLC to an effective pro-oxidant agent.…”
Section: Discussionmentioning
confidence: 99%